E-GOVERNMENT AND PUBLIC TRUST: EXAMINING THE IMPACT OF DIGITAL TRANSPARENCY ON CITIZEN ENGAGEMENT IN SOUTHEAST ASIA - Maulan, Puteri Anindya; Fitriani, Nining (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
Digital transformation in the public sector through the implementation of e-government offers significant opportunities to enhance transparency and citizen engagement. This study analyzes the impact of digital transparency on public trust and citizen participation in Southeast Asia, focusing on Indonesia, Malaysia, and Thailand. A conceptual model was developed based on three main theories: Digital Transparency Theory, Institutional Trust Theory, and Digital Divide Theory. The research adopts a Design Science Research approach, utilizing both quantitative and qualitative methods. Data were collected through a survey of 600 respondents and in-depth interviews with 15 key stakeholders. The analysis was conducted using Structural Equation Modeling (SEM-PLS) with SmartPLS 4.0. The results indicate that digital transparency has a significant effect on public trust (β = 0.624), which in turn increases citizen participation (β = 0.538). Government reputation serves as a positive mediator (β = 0.293), while the digital divide acts as a negative moderator (β = -0.146), hindering the effectiveness of transparency in areas with limited digital access. These findings underscore the need for digital literacy strategies and the design of more inclusive e-government systems. The study provides both theoretical and practical contributions to understanding the dynamics of e-government in developing countries and promotes sustainable citizen engagement through equitable digital transparency approaches.